Integration of Artificial Intelligence and Human Communication in Managerial Decision Making - Lilis Yuningsih; Dadang Hermawan; I Made Darsana (Yayasan Darussalam Bengkulu, 2026)
Background: The development of digital transformation has encouraged modern organizations to utilize artificial intelligence to improve decision-making effectiveness. However, the implementation of AI in organizations still requires the support of human communication to ensure effective information interpretation, organizational coordination, and the quality of managerial decisions. This study aims to analyze the effect of the integration of artificial intelligence and organizational communication on managerial decision-making in hospitality companies in Java and Bali. Method: This study employed a quantitative approach with an explanatory research design. Data collection involved distributing questionnaires to 182 respondents, consisting of managers, supervisors, and professional staff in service, hospitality, education, and digital companies in Java and Bali. Data analysis used multiple linear regression with SPSS. Results: The results of the study indicate that Artificial Intelligence has a positive and significant effect on managerial decision-making with a significance value of 0.000 < 0.05. Human communication also has a positive and significant effect on managerial decision-making with a significance value of 0.001 < 0.05. Simultaneously, artificial intelligence and human communication have a significant effect on managerial decision-making with a coefficient of determination of 64.8%. The results of the study indicate that the integration of AI and human communication is the most appropriate approach in creating an effective decision-making system based on human-centered management in the era of digital transformation. Conclusion: This research provides theoretical contributions to the development of technology communication and digital management studies and provides practical implications for organizations in optimizing the use of AI by strengthening organizational communication.